2009
DOI: 10.4049/jimmunol.0900007
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Action of Rheumatoid Arthritis Synovial Fibroblast IL-15 Expression on the Equilibrium between CD4+CD25+ Regulatory T Cells and CD4+CD25− Responder T Cells

Abstract: We previously described that fibroblast-like cells from the synovium of rheumatoid arthritis patients (RASFib) constitutively express intracellular and surface IL-15, which induces activation of cocultured T cells. Our objective was to study the effect of RASFib IL-15 expression on the function of human CD4+CD25+ regulatory T cells (Treg). RASFib, through their constitutive IL-15 expression, were able to induce the proliferation of human Tregs stimulated through their TCR, and at the same time potentiated thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
70
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 59 publications
13
70
0
Order By: Relevance
“…The first step was to determine whether IL-15 was able to affect the Th1/Th2 balance of CD4 T cells. It has previously been shown that IL-15 can cause proliferation of CD4 T cells (naive and/or memory), and there are contrasting results as to whether it promotes T regulatory cells or highly active Th1 CD4 T cells (29,30,32). This lack of consensus between studies is most likely due to the different in vitro and in vivo conditions under which they investigated the effect.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The first step was to determine whether IL-15 was able to affect the Th1/Th2 balance of CD4 T cells. It has previously been shown that IL-15 can cause proliferation of CD4 T cells (naive and/or memory), and there are contrasting results as to whether it promotes T regulatory cells or highly active Th1 CD4 T cells (29,30,32). This lack of consensus between studies is most likely due to the different in vitro and in vivo conditions under which they investigated the effect.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, some report that it can prime naive T cells, whereas others report effects only on memory CD4 T cells (29)(30)(31). Some find that IL-15 can promote the formation of T regulatory cells, but that it also increases the proliferation and cytokine secretion of IFN-g-producing CD4 and CD8 T cells so that the T regulatory cells were unable to inhibit the T cells (32,33). In contrast, it was recently found that, in mice that lack the receptor for IL-15 signaling (IL-15Ra 2/2 ), CD4…”
mentioning
confidence: 99%
“…Although the contribution of IL-15 to the development and regulation of autoimmune disease has not been clearly defined (34)(35)(36)(37)(38), low doses of IL-15 may allow selective expansion of CD8 + Tregs in vivo. A precedent for such an approach is suggested by recent reports that low-dose IL-2 treatment selectively enhances CD4 + Tregs in vivo and can suppress chronic graft-versus-host disease (GVHD) and HCV-related vasculitis after BM transplants (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…5-7 ), which might spatially interfere with the expansion or migration of FOXP3 + cells into this area. Alternatively, although not mutually exclusive, cytokines, such as IL-10 [32] and IL-15 [33] , which selectively activate Tregs, could preferentially be secreted in the LP mucosa, thus inducing FOXP3 + cell expansion. Studies designed to reveal the presence of the described cytokines in the epithelial mucosa of celiac patients are also currently underway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these cells exhibit regulatory function in human and murine models of autoimmunity [9,17] as well as in cancer [18] . Tregs are regulated by cytokines, such as IL-15 [19] , which maintain their optimal regulatory function in a phosphatidylinositol 3-kinase-dependent manner [20] and induce Treg proliferation through interaction with their T-cell receptor [21] .…”
Section: Introductionmentioning
confidence: 99%